Field reports form for submitting seasonal observations of Iowa birds, Fred Lesher, fall 1983 - Lesher, Fredet al (1983)
An annotated list of birds sighted by Fred Lesher. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed